IMPACT OF SIGNIFICANT WAVE HEIGHT, WIND SPEED, AND PRECIPITATION VARIABILITY ON SHIPPING SAFETY IN INDONESIAN ARCHIPELAGIC SEA LANES - Fathurohman, Azkal; Napitupulu, Gandhi; Fujiawati, Ghina; Napitupulu, Moses (BULLETIN OF THE MARINE GEOLOGY, 2025)
Unexpected and unpredictable extreme weather poses significant risks to maritime activities, particularly in Indonesian waters and the Indonesian Archipelagic Sea Lanes, known as ALKI, which have been internationally recognized for shipping and aviation since 1985. This study assesses these risks by analyzing patterns of wave height, wind speed, and rainfall along ALKI to improve shipping safety and mitigate accident risks. Data from the European Centre for Medium-Range Weather Forecasts (ECMWF) ERA5 for the period 1993 to 2023 and Global Precipitation Measurement (GPM) for 2001 to 2020 were processed using descriptive statistics and Empirical Orthogonal Function (EOF) methods. The results reveal high waves (1-2.5 m) and strong winds at Beaufort scale 4 prevailing in northern Indonesian waters from December to February and southern waters from June to August. Higher rainfall (350-600 mm) occurs in the northern region from September to November and in the southern from December to February. Extreme waves (90th percentile) reach up to 3 m in open ocean areas such as the Natuna Sea, western Sumatra, southern Java, the Maluku Sea, and northern Papua Sea. Extreme winds are observed over open ocean areas, with slight spatial shifts, as seen in the Arafura Sea (9-10 m/s). Extreme rainfall (250-350 mm) is concentrated in the northwestern region. EOF analysis identifies global climate phenomena and regional oceanographic dynamics as the primary drivers of significant wave height variability. Improved understanding of weather variability can enhance navigation safety along the ALKI routes and inform more effective regulation, law enforcement, and monitoring.